Adopsi Inovasi Budidaya Bawang Merah Pada Petani Bawang Merah di Kelurahan Toapaya Asri Kecamatan Toapaya Kabupaten Bintan - Sharin Ikka Nurmaida; Susy Edwina; Roza Yulida (Jurnal Sosial Ekonomi Pertanian, 2023)
Shallots are one of the main commodities in Indonesia. Consumption needs and demand that tend to increase are a potential market opportunity for farmers to increase shallots production. The purpose of this research was to ascertain the process of shallot cultivation innovation adoption and to analyze the rate of adoption of farmers who apply innovations in shallot cultivation. This research was conducted in Toapaya Asri Village, Toapaya District, Bintan Regency, determined purposively, with the consideration that this area has been cultivating shallots and is still running until now. The respondents were selected using the census method, with a maximum of 15 shallot farmers as respondents, taking into account that farmers continue to cultivate shallots. The findings indicated that the innovation adoption process of shallots could be divided into five stages: the knowledge stage was categorized as high, the persuasion stage was categorized as high, the adoption decision stage was categorized as very high, the decision not to adopt was categorized as very low, the implementation stage was categorized as high, and the confirmation stage was categorized as high. Overall, The level of adoption of innovations by farmers who implement shallot cultivation is in the very high category. Keywords: Adaptation; Innovation; Shallot Cultivation.